Understanding Indian policy dilemmas in the Indo-Pacific through an India–US–China maritime triangle lens. (2nd January 2016) - Ollapally, Deepa M.
ABSTRACT: Between the American rebalance strategy and Chinese Maritime Silk Road initiative, India is increasingly pressed to formulate a maritime strategy that ideally meets Indian economic and strategic objectives. This is generating major policy dilemmas for India stemming from the attraction of economic integration led by China on the one hand, versus the attraction of strategic integration offered by the United States on the other hand. This paper suggests that between these binary options, there are both opportunities and challenges for India, calling for fine-grained policymaking. The notional concept of an India–US–China maritime triangle is useful in sifting through the choices before India to meet its ambitions of development as well as retain and improve its strategic influence in the Indian Ocean and beyond.